Allograft rejection mediated by memory T cells is resistant to regulation. - Yang, J; Brook, M; Carvalho-Gaspar, M; Zhang, J; Ramon, H; Sayegh, M; Wood, K; Turka, L; Jones, N (2007)
Alloreactive memory T cells may be refractory to many of the tolerance-inducing strategies that are effective against naive T cells and thus present a significant barrier to long-term allograft survival. Because CD4(+)CD25(+) regulatory T cells (Tregs) are critical elements of many approaches to successful induction/maintenance of transplantation tolerance, we used MHC class I and II alloreactive TCR-transgenic models to explore the ability of antigen-specific Tregs to control antigen-specific memory T cell responses. Upon coadoptive transfer into RAG-1(-/-) mice, we found that Tregs effectively suppressed the ability of naive T cells to reject skin grafts, but neither antigen-unprimed nor antigen-primed Tregs suppressed rejection by memory T cells. Interestingly, different mechanisms appeared to be active in the ability of Tregs to control naive T cell-mediated graft rejection in the class II versus class I alloreactive models. In the former case, we observed decreased early expansion of effector cells in lymphoid tissue. In contrast, in the class I model, an effect of Tregs on early proliferation and expansion was not observed. However, at a late time point, significant differences in cell numbers were seen, suggesting effects on responding T cell survival. Overall, these data indicate that the relative resistance of both CD4(+) and CD8(+) alloreactive memory T cells to regulation may mediate resistance to tolerance induction seen in hosts with preexisting alloantigen-specific immunity and further indicate the multiplicity of mechanisms by which Tregs may control alloimmune responses in vivo.